The double-stranded DNA-binding proteins TEBP-1 and TEBP-2 form a telomeric complex with POT-1 - Sabrina Dietz (Nature Portfolio, 2021)
Telomeres, tandem repeats at the ends of linear chromosomes, have evolved to deal with the end replication and end protection. Using a proteomics approach, the authors identify TEBP-1 and TEBP-2, two double-stranded binding proteins which together are required for fertility. Despite being paralogs, they have distinct individual effects on telomere dynamics; TEBP-1 and TEBP-2 are part of a telomeric complex also containing POT-1.